Yb-doped fiber laser system with 1kW, 10mJ and <300fs pulse for the generation of TW class few-cycle pulses - Breitkopf, Sven; Hädrich, Steffen; Kienel, Marco; Jójárt, Péter; Várallyay, Zoltán; Osvay, Károly; Simon, Peter; Nagy, Tamas; Blumenstein, Andreas; Klas, Robert; Buldt, Joachim; Stark, Lars Henning; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
We present a 10-mJ and 1-kW, sub 300-fs CPA system with excellent beam quality (M2=1.1). To achieve such parameter-set, the output of 16 main-amplifier channels is coherently combined using a polarization-based filled-aperture scheme. The system exhibits excellent long-term stability of 0.3% RMS power fluctutations over >9hours and is a major part of the ELI-ALPS HR2 laser system. It will be combined with a nonlinear pulse compression unit that aims to achieve 5 mJ pulse energy at 100 kHz pulse repetition rate (i.e. 500 W of average power) and with pulse durations of 6 fs, i.e. a terawatt class laser. In addition to the CPA system we present first promising experimental results on compression of high energy pulses with high average power in a long stretched capillary setup. In a first proof-of-principle experiments, 5 mJ pulses at 100 kHz (500 W average power) are spectrally broadened in a 4 m long capillary to a bandwidth supporting <17 fs pulses. Further experimental results towards the achievement of the HR2 pulse parameters will be presented at the conference.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coherent pulse combining; Few-cycle pulses; Fiber laser; High power laser; High repetition-rate; Terawatt